Pelatihan Musikalisasi Gurindam Sebagai Upaya Pendidikan Karakter Bagi Siswa SMA - Aprilia, Maya; Suparman, Suparman; Eliana, Evi; Khairunnissa, Khairunnissa; Sugiarti, Sugiarti (University of Islam Malang, 2020)
The Student Creativity Program in the field of community service aims to provide character education to students and preserve Indonesian literary culture through musical training in Gurindam. This activity was carried out for five months in Assanadiyah High School Palembang led by Mr. Kasbun Dahir, S.Pd, M.Sc. The number of partner members in this activity is 10 people, namely class XI IPA. The method used in this activity consists of; preparation and counseling, assignments and training, presentations and performances, and evaluation. The results obtained are 92% of students aware of the importance of loving the local culture and 86% of students are able to compose gurindam and the formation of gurindam literary studio named Sanggurdiyah. Thus this activity provides a major influence on the importance of loving the local culture.